A comparison of biomarkers of organ damage between full and half Ironman triathlon competitions - Cottrell, G. T.; Migotto, B. (Applied Physiology, Nutrition, and Metabolism, 2018)
The purpose of this study was to compare changes in biomarkers of organ damage and inflammation in athletes competing in Ironman triathlon events of different distances. 19 ultra-endurance athletes were recruited along with 13 non-exercising volunteers (CON). 12 athletes competed in the 70.3 mile half Ironman (HIM) while 13 athletes participated in the 140.6 mile full Ironman (FIM). Athletes provided blood and urine samples 1 hour prior to, and following, the competition. Samples were analyzed for changes in biomarkers of heart, kidney and liver damage. Biomarkers that were significantly higher in the FIM vs HIM group included; skeletal muscle creatine kinase (1592.3 vs 254.8%), cardiac creatine kinase (1798% vs 233%), liver AST (153.3 vs 52.2%) and tumor necrosis factor alpha (220 vs 80%). Biomarkers that were higher in the HIM vs FIM group included; cardiac troponin (1700% vs 315%), plasma creatinine (57.4 vs 32.9%) and blood urea nitrogen (17.4 vs 1.9%). Urine microalbumin was significantly higher than CON in both HIM and FIM, however there were no differences between athlete groups (CON=19.4%, HIM=1138%, FIM=10090%). FIM had higher numbers of red and white blood cells in the urine when compared to HIM. In conclusion, overall markers of damage are higher in the FIM vs HIM group suggesting a volume mediated response, however this was not consistent for all markers, and there was significant variability in individual responses.